Toward an understanding of economic growth in Africa: A reinterpretation of the Lewis model - Diao, Xinshen; McMillan, Margaret S. (Elsevier, 2018)
We develop a model economy that has many of the features of Lewis (1954) but that also includes an in-between sector as described by Lewis (1979). Our model underscores the importance of the following determinants of structural change: (i) productivity growth in the agricultural sector; (ii) productivity growth in the nonagricultural sector and; (iii) the terms of trade. Public investment enhances productivity growth in all sectors but when it is financed by foreign inflows, it also causes a real exchange rate appreciation leading to a contraction in the open modern sector. These results provide a partial explanation for recent patterns of growth in Rwanda and elsewhere in Africa where the nontradables or what we call the in-between sector has expanded more rapidly than the tradable sector. Our results also highlight the dilemma faced by poor countries in dire need of public investment with a very limited tax base.